Karakter Ibu Tiri Selalu Jahat? (Studi Perbandingan Cerita Rakyat Indonesia) - Aurelius Ratu (Jurnal Sosial Humaniora, 2017)
The story of the stepmother in almost all cultures often describes her as evil,ambitious, and cruel. This paper presents a comparative study of twoIndonesian folklore that presents the theme of stepmother. Through astructural and sociological approach, it is found that the storyline is notmuch different from the folktale of the stepmother in general. Whatdistinguishes it is the heroic or supernatural part of it gets less emphasiseven though it still remain exists. Apparently, such stories need specialattention (revision), especially for the formation of a stepmother image inthe midst of society so that negative stigma does not adversely affect thechild's life